Challenges to achieving and maintaining viral suppression among children living with HIV. (1st April 2020) - Kakkar, Fatima; Lee, Terry; Hawkes, Michael T.; Brophy, Jason; Lindy, Samson; Singer, Joel; Dieumegard, Hinatea; Sauve, Laura; Alimenti, Ariane; Vaudry, Wendy; Seigel, Sandra; Tan, Ben; et al.
Abstract : Objectives: The objective of this study was to determine the time to, and durability of, viral suppression, among Canadian children living with HIV after initiation of combination antiretroviral therapy (cART). Design: Prospective, multicenter Canadian cohort study (Early Pediatric Initiation Canada Child Cure Cohort), using both prospective and retrospectively collected data. Methods: Kaplan–Meir survival estimates with Cox regression were used to determine the time to and risk factors for viral suppression, defined as two consecutive undetectable viral loads (<50 copies/ml) at least 30 days apart after initiation of cART. Results: A total of 228 children were enrolled between December 2014 and December 2018. The time to viral suppression was significantly shorter among children initiating cART after 5 ⩽ 5 vs. years or less of age [adjusted hazard ratio (aHR) 1.57, 95% confidence interval (CI) 1.13–2.20], among those born after 2010 vs. prior (aHR 1.71, 95% CI 1.04–2.79), and among those without child protection services involvement (aHR 1.44, 95% CI 1.03–2.01). Overall, 27% of children had a viral rebound within 3 years of achieving viral suppression; the risk of viral rebound was significantly lower among children initiating cART after 5 vs. 5 years or less of age [adjusted odds ratio (aOR): 0.32, 95% CI 0.13–0.81], those whose families had not received social assistance (aOR 0.16, 95% CI 0.06–0.46), and females vs. males (aOR 0.51, 95% CI 0.26–0.99). Conclusion: Only 73% of the children in the Early Pediatric Initiation Canada Child Cure Cohort had maintained viral suppression 3 years after it was first achieved. Age at cART initiation, and socioeconomic factors were predictors of both time to viral suppression and risk of viral rebound in this cohort.